Strong but not Broadly Shared Growth. Mozambique Poverty Assessment - World Bank (World Bank, 2018)
Mozambique has recorded strong growth, but many low-income households are missing out on the benefits and policy options to make rowth more inclusive in Mozambique
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; poverty / pobreza

Reality checks in Mozambique: building better understanding of the dynamics of poverty and well-being. Final Report 2011-2015 - Tvedten, Inge; Tuominen, Minna; Rosário, Carmeliza (ORGUT Consulting AB, 2016)
A series of five “Reality Checks” will take place in the period 2011-2016, focussing on the dynamics of poverty and well-being with a particular focus on good governance, agriculture/climate and energy that are key sectors in Swedish development cooperation with Mozambique. Each Reality Check will be published in the form of one Annual Report and three Sub-Reports from each of the three selected study-sites (see ORGUTa 2011 for more details). More concretely, the “Reality Checks in Mozambique” are expected to: i) Inform the public discussion among key development actors on poverty reduction, especially in the province of Niassa; ii) Contribute to a better understanding of qualitative poverty monitoring methods in Mozambique; iii) Provide Sweden with relevant qualitative data on developments and results from its engagement in Mozambique and support further implementation of its programme in Niassa. The series of studies was initiated by an Inception Report published in August 2011 (ORGUT 2011a). Through that exercise, it was decided that the Reality Checks shall be based on fieldwork in three different Districts/Municipalities in the Province of Niassa that display variations in terms of geographical locations, access to public services and levels of poverty and well-being. The three areas selected were i); the Municipality of Cuamba; ii) the District of Lago and iii) the District of Majune (see Map 1). The 1 st Reality Check was carried out in 2011 in the form of three sub-reports (Orgut 2011 b,c,d) and the first Annual Report (Orgut 2011 e), and represent a baseline upon which the subsequent Reality Checks will build. This is the Annual Report for the 2 nd Reality Check, synthesising the main findings from the Cuamba, Lago and Majune sub-reports. In addition to pursuing the overall issue of the dynamics of poverty and well-being, this year’s reports have a thematic focus on governance.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Cuamba; GD - Lago; GD - Majune; GP - Niassa; L - english / inglês; M - evaluation / avaliação; agriculture / agricultura; gender / género; institutions / instituições; poverty / pobreza; private sector / setor privado

Reality checks in Mozambique: building better understanding of the dynamics of poverty and well-being. Annual Report, Year Three, 2013 – Agriculture, Climate and Employment - Tvedten, Inge; Rosário, Carmeliza; Tuominen, Minna; Samuel Jones (ORGUT Consulting AB, 2013)
A series of five “Reality Checks” will take place in the period 2011-2016, focussing on the dynamics of poverty and well-being with a particular focus on good governance, agriculture/climate and energy that are key sectors in Swedish development cooperation with Mozambique. Each Reality Check will be published in the form of one Annual Report and three Sub-Reports from each of the three selected study-sites (see ORGUTa 2011 for more details). More concretely, the “Reality Checks in Mozambique” are expected to: i) Inform the public discussion among key development actors on poverty reduction, especially in the province of Niassa; ii) Contribute to a better understanding of qualitative poverty monitoring methods in Mozambique; iii) Provide Sweden with relevant qualitative data on developments and results from its engagement in Mozambique and support further implementation of its programme in Niassa. The series of studies was initiated by an Inception Report published in August 2011 (ORGUT 2011a). Through that exercise, it was decided that the Reality Checks shall be based on fieldwork in three different Districts/Municipalities in the Province of Niassa that display variations in terms of geographical locations, access to public services and levels of poverty and well-being. The three areas selected were i); the Municipality of Cuamba; ii) the District of Lago and iii) the District of Majune (see Map 1). The 1 st Reality Check was carried out in 2011 in the form of three sub-reports (Orgut 2011 b,c,d) and the first Annual Report (Orgut 2011 e), and represent a baseline upon which the subsequent Reality Checks will build. This is the Annual Report for the 2 nd Reality Check, synthesising the main findings from the Cuamba, Lago and Majune sub-reports. In addition to pursuing the overall issue of the dynamics of poverty and well-being, this year’s reports have a thematic focus on governance.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Cuamba; GD - Lago; GD - Majune; GP - Niassa; L - english / inglês; M - evaluation / avaliação; agriculture / agricultura; institutions / instituições; poverty / pobreza

Reality checks in Mozambique: building better understanding of the dynamics of poverty and well-being. Annual Report, Year One - Tvedten, Inge (ORGUT Consulting AB, 2012)
he Reality Checks are implemented 2011-2016 and each year field work is carried out in the Municipality of Cuamba, the District of Lago and the District of Majune in the Niassa Province. This is the Annual Report for Year One of the Reality Checks and aims at summarising the conclusions based on the findings from the field sub-report from each study location.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Cuamba; GD - Lago; GD - Majune; GP - Niassa; L - english / inglês; M - evaluation / avaliação; agriculture / agricultura; gender / género; poverty / pobreza

‘Opitanha’ Revisited Assessing the Implications of PARPA II in Rural Northern Mozambique 2006-2009 - Tvedten, Inge; Paulo, Margarida; Rosário, Carmeliza (Chr. Michelsen Institute, 2010)
This report is part of the efforts to monitor and evaluate the implications of Mozambique’s Poverty Reduction Strategy PARPA II (GdM 2005). Three qualitative and participatory studies have already been carried out in three different areas of the country: One in the District of Murrupula in Nampula Province (Tvedten, Paulo & Rosário 2006); one in four bairros in the capital Maputo (Paulo, Rosário & Tvedten 2007); and one in the district of Buzi in Sofala Province (Rosário, Tvedten & Paulo 2008). Each of these studies is to be followed up in order to ascertain changes in social relations and cultural perceptions of poverty and well-being, by visiting the same local administrations, the same communities and the same households after a period of three years. This report is the first in the series of the three such follow-up studies, with the Maputo and the Buzi studies planned for 2010 and 2011, respectively.
Keywords: *tagged; G - Mozambique / Moçambique; G - central / centro; G - north / norte; G - south / sul; GD - Murrupula; GP - Maputo; GP - Nampula; L - english / inglês; M - evaluation / avaliação; agriculture / agricultura; education / educação; poverty / pobreza; social inclusion & exclusion / inclusão e exclusão social; urbanization / urbanização

Niassa Agricultural Development Project (NADP): Completion Evaluation - International Fund for Agricultural Development (International Fund for Agricultural Development, 2007)
Evaluation report of IFAD's Niassa Agricultural Development Project (NADP).
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Lichinga; GP - Niassa; L - english / inglês; agriculture / agricultura; infrastructure - roads / infrastructura - estradas; infrastructure / infrastrutura; poverty / pobreza

"Opitanha:" Social Relations of Rural Poverty in Northern Mozambique - Tvedten, Inge; Paulo, Margarida; Rosário, Carmeliza (Chr. Michelsen Institute, 2006)
Research-based information is recognised as crucial for Mozambique's endeavours to reduce its poverty. This first report in a series of three qualitative studies on poverty in Mozambique focuses on the district of Murrupula in Nampula province. In Chapter 1 we argue that qualitative studies are important for the monitoring and evaluation of poverty reduction policies. They inform quantitative data and correlations by testing causal hypotheses on the ground. They discover processes and interdependencies related to non-tangible dimensions of poverty such as vulnerability and powerlessness. They test and reassess central concepts and units of poverty analysis. Finally, they involve the poor themselves in the analysis of their own situation in ways that are difficult with formal questionnaire surveys. In Chapter 2 we present central quantitative expressions of poverty in Mozambique as points of reference. We start by outlining some of the broad development trends, including urbanisation, feminisation of poverty and HIV/AIDS, and then analyse data on Mozambique and Nampula to highlight similarities and differences. Chapter 3 provides a background profile of the area under study, predicated on the assumption that the political, economic and sociocultural context is important for understanding social relations of poverty. A brief history emphasising how Murrupula was constrained in its development through the late colonial era, the Frelimo socialist experiment and the war leads into an outline of the responsibilities of the District Administration, the role of traditional authorities, and the overall social and economic situation in the district. Chapter 4 is built around the survey undertaken for this study, and outlines socioeconomic conditions and determinants of poverty with a focus on employment and income, education and health. It also looks at the implications of geographical space, especially distance from the main economic and population centres, for poverty and poverty alleviation. Chapter 5 focuses on the issue of social relations of poverty, and processes of impoverishment, marginalisation and social exclusion. Its point of departure is people's own emic perceptions of poverty, examining relationships between different categories of the poor within the household and the extended family, traditional institutions and the state. Chapter 6 concludes, drawing some preliminary policy implications and outlining the planned follow-up of the current study in urban Maputo and coastal Sofala respectively.Research-based information is recognised as crucial for Mozambique's endeavours to reduce its poverty. This first report in a ser...
ISSN 0805-505X ISBN 82-8062-172-5
Keywords: *indexed; *snowball; *tagged; G - Mozambique / Moçambique; G - central / centro; G - north / norte; G - south / sul; GD - Murrupula; GP - Nampula; L - english / inglês; agriculture / agricultura; education / educação; poverty / pobreza; social inclusion & exclusion / inclusão e exclusão social; urbanization / urbanização

Malonda – The Private Sector Support related to Agriculture in Niassa - Carlsson, Lars (SIDA - The Swedish International Development Cooperation Agency, 2003)
Information on the Swedish support to the private sector related to agriculture in Niassa, Mozambique 2003.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; agriculture / agricultura; poverty / pobreza; private sector / setor privado